A Fifty Year Intrauterine Contraception Odyssey - Goldstuck, Norman D. (New Horizons in Medicine and Medical Research Vol. 12, 2022)
Modern IUDs began with the thermoplastic variety and extended to copper based and then progestin based varieties. Originally due to the absence of formal regulations many different sizes and types of IUD were manufactured. Nowadays due to strict regulations there are very few innovations in IUD research. For this reason current practitioners are unlikely to have the experience that I have had. This review describes the developments in IUD research from the inert plastic devices then to copper bearing devices and finally to the modern progestin containing IUDs from the experience of one researcher over a 50 year timespan. Much of this experience has been the subject of numerous publications in peer reviewed journals. The article chronicles the use of 15 different types of IUD and their subtypes, some 30 different sizes in all.